REKAYASA ULANG PROSES BISNIS (BUSINESS PROCESS REENGINEERING) UNTUK MENCAPAI SIMPLIFYING THE AIRLINES BUSINESS - M. Nur Nasution (Media Riset Bisnis & Manajemen, 2006)
Business process reengineering (BPR) is one of the efforts to increase superiority compatative incentives. BPR will simplyffyd process of service passangers without decrease of comfortable and safety passangers, until operabon cost can push down. Today by airlines business develops simplifying airline business using of electronic technology to serve passengers, To achieve low cost as much as possible and gives passenger simplifying in use of air transport services